2007
DOI: 10.1016/j.biopsycho.2007.06.002
|View full text |Cite
|
Sign up to set email alerts
|

Emotion regulation in emerging adult couples: Temperament, attachment, and HPA response to conflict

Abstract: Difficulty managing the stress of conflict in close relationships can lead to mental and physical health problems, possibly through dysregulation of the hypothalamic-pituitary-adrenal (HPA) axis, the neuroendocrine stress response system. Temperament, an individual characteristic, and attachment, a dyadic characteristic, have both been implicated in emotion regulation processes and physiological reactivity, yet there is no clear consensus on how the two work together to influence the stress response, especiall… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
78
0
1

Year Published

2011
2011
2020
2020

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 94 publications
(82 citation statements)
references
References 53 publications
3
78
0
1
Order By: Relevance
“…As Mikulincer and Shaver described previously, avoidant individuals inhibit their emotional experience (Shaver & Mikulincer, 2007). Although high levels of avoidance seemed to dampen (short-term) negative effects on self-reported affect, long-term health and relationship effects of avoidance may still be negative (e.g., Laurent & Powers, 2007;Stanton & Campbell, 2014). There might be opposite patterns for physiological stress reactions as Diamond et al have shown signs of repressive coping for highly avoidant individuals in reaction to different tasks (2006).…”
Section: Discussionmentioning
confidence: 99%
“…As Mikulincer and Shaver described previously, avoidant individuals inhibit their emotional experience (Shaver & Mikulincer, 2007). Although high levels of avoidance seemed to dampen (short-term) negative effects on self-reported affect, long-term health and relationship effects of avoidance may still be negative (e.g., Laurent & Powers, 2007;Stanton & Campbell, 2014). There might be opposite patterns for physiological stress reactions as Diamond et al have shown signs of repressive coping for highly avoidant individuals in reaction to different tasks (2006).…”
Section: Discussionmentioning
confidence: 99%
“…In related work, Laurent and Powers (2007) found that men's attachment avoidance and emotional temperament (assessed using subscales of distress, fearfulness and anger) interacted to predict their own and their female dating partners' cortisol levels during conflict. Men's cortisol levels were highest during conflict when they were high in avoidance and low in emotionality, while women's cortisol levels were highest when their partners were low in avoidance and high in emotionality.…”
Section: Physiological Response To Relationship Threat and Attachmentmentioning
confidence: 99%
“…Cabe anotar que ante conflictos familiares y separaciones más prolongadas, estos niños sí parecen tener respuestas del eje HPA (Del Giudice et al, 2011). Por el contrario, los niños con apego seguro han mostrado menores niveles de cortisol basales y menor reactividad adrenocortical al estrés (Laurent & Powers, 2007).…”
Section: Impacto Del Apego En Los Procesos De Salud/enfermedadunclassified